Survey of Post-Harvest Fungal Diseases of Some Fruits from Marathwada Regions of Maharashtra, India - Rathod*, G.M. (Journal of Ecobiotechnology, 2010)
Present paper deals with the survey of post-harvest fungal diseases of tropical fruits like mango, grapes and anola in the year 2009-2010. Penicillum rot; Aspergillus niger rot, Rhizopus rot, Phomopsis rot were common diseases of mango, anola and grapes. — Department of Botany, Shrikrishna Mahavidyalaya, Gunjoti, Dist.Osmanabad (M. S.), India — Please Cite This Article As: Â G.M. Rathod. 2010. Survey of Post-Harvest Fungal Diseases of Some Fruits from Marathwada Regions of Maharashtra, India. J. Ecobiotechnol. 2(6):7-10. Â